Using e-portfolio for learning goal setting to facilitate self-regulated learning of high school students. Issue 12 (2nd December 2018) - Chang, Chi-Cheng; Liang, Chaoyun; Chou, Pao-Nan; Liao, Yueh-Mai
ABSTRACT: This study aims to explore the influence of using e-portfolio for learning goal setting on self-regulated learning. The subjects were 40 second-year students (18 males and 22 females) taking the 'Webpage Design' course of the Department of Information Technology in a vocational high school. The experimental teaching lasted for ten weeks, and the students used e-portfolio for learning goal setting. The t -test result showed that the students' self-regulated learning after using e-portfolio for learning goal setting is better than that before goal setting. The regression result showed that goal setting performance significantly and positively influences self-regulated learning. In other words, having goal setting or better goal setting leads to better self-regulated learning. Finally, limitation and recommendations for future work are proposed.